Pengaruh Dari Dampak Manajemen Laba Rill Dan Akrual Serta Penghindaran Pajak Terhadap Nilai Perusahaan Dengan Mekanisme Tata Kelola Perusahaan Sebagai Moderasi - Erwan Hidayat; Jaelani Jaelani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Main Problem: Real and Accrual Profit Management and Tax Avoidance in Companies Affect Company Value with Corporate Governance Mechanisms as Moderating. Objectives: 1. To determine the impact of real and accrual profit management and tax avoidance on the influence of company value; 2. To find out the impact of real and accrual profit management and tax avoidance on the influence of company value with the Corporate Governance Mechanism as Moderation. Originality: Testing the Effect of the Impact of Real and Accrual Profit Management and Tax Avoidance with the Corporate Governance Mechanism as Moderation. Method: The population in the research conducted was 171 companies, of which 171 companies were listed on the CGPI and BEI Index in a 6 year time span, namely 2017-2022. The technique used in the research carried out was the purposive sampling method. Results: After conducting the research, it was found that Real and Accrual Profit Management and Tax Avoidance Produce a Positive Influence, which means it has an influence on Company Value. Likewise, with the Corporate Governance mechanism as Moderation, Real Profit Management and Accruals and Tax Avoidance produce a Positive Influence, which means it has an influence on Company Value.